Impact of Rice Husk Biochar on Growth, Water Relations and Yield of Maize (Zea mays L.) under Drought Condition (The Agriculturists, 2018)
The present experiment was conducted to study the impact of rice husk biochar on growth, water relations and yield of maize (BARI Hybrid Bhutta- 9) under drought (60 and 40% of FC) conditions. Four doses of rice husk biochar @ 0, 5, 10 and 20 t/ha were applied as an amendment in soil before sowing of seeds. Results revealed that drought stress reduced plant height, relative water content and grain yield of maize. But rice husk biochar at different doses improved the above mentioned characters under drought conditions. Under 60% of FC, the highest plan height, leaf water content and yield were 196.67 cm, 79.86% and 89.75 g/plant, respectively when biochar was applied @ 20 t/ha but it was 173.33 cm, 78.32% and 84.57 g/plant, respectively under 40% of FC when biochar was applied at the same dose. It may be concluded that, rice husk biochar @ 20 t/ha showed the best result to promote growth, water relation traits and yield of maize under drought condition.The Agriculturists 2018; 16(2) 93-101